Effect of Income Diversification on Risk-Adjusted Profitability of Commercial and Development Banks in Nepal - Prajapati, Rubina; Shah, Ajay Kumar (Journal of Business and Social Sciences Research, 2019)
This study analyses the impact of income diversification on risk adjusted profitability of commercial and development banks in Nepal. Risk adjusted profitability is measured in terms of risk adjusted return on assets (RAROA) and risk adjusted return on equity (RAROE). The regression analysis shows Herfindahl Hirschman Index (HHI), equity multiplier, non-interest income and foreign holding have significant positive impact on RAROE of commercial banks. Whereas the size of commercial banks has a significant negative impact on RAROE. There is a significant positive impact of HHI, non-interest income on RAROA in case of commercial banks. Size of commercial banks also has a significant negative impact on RAROA. Debt ratio does not have significant impact in case of RAROE of commercial banks and equity multiplier, debt ratio and foreign holding do not have significant impact on RAROA of commercial banks. The regression analysis of development banks showed there is significant positive impact of HHI and equity multiplier on RAROE of development banks. The study concludes that income diversification, non-interest income and size of the commercial banks are the major determinants of risk adjusted profitability of commercial banks.